I am Abraham : (a novel of Lincoln and the Civil War) - Charyn, Jerome (Liveright Publishing Corporation, A Division of W.W. Norton & Company, 2014)
Traces the historic arc of Lincoln's life from his picaresque days as a gangly young lawyer in Sangamon County, Illinois, through his improbable marriage to Kentucky belle Mary Todd, to his 1865 visit to war-shattered Richmond only days before his assassination.